Visualizing and quantifying 33P uptake and translocation by maize plants grown in soil - Holz, Maire; Mundschenk, Eva; Pusch, Valerie; Remus, Rainer; Dubbert, Maren; Oburger, Eva; Staudinger, Christiana; Wissuwa, Matthias; Zarebanadkouki, Mohsen (Frontiers in Plant Science, 2024)
Phosphorus (P) availability severely limits plant growth due to its immobility and inaccessibility in soils. Yet, visualization and measurements of P uptake from different root types or regions in soil are methodologically challenging. Here we explored the potential of phosphor imaging combined with local injection of radioactive 33 P to quantitively visualize P uptake and translocation along roots of maize grown in soils.Rhizoboxes (20x40x1 cm) were filled with sandy field soil or quartz sand, with one maize plant per box. Soil compartments were created using a gravel layer to restrict P transfer. After two weeks, a compartment with the tip region of a seminal root was labeled with a NaH2 33 PO4 solution containing 12 MBq of 33 P. Phosphor imaging captured root P distribution at 45, 90, 135, 180 minutes, and 24 hours post-labeling. After harvest, 33 P levels in roots and shoots were quantified.P uptake exhibited a 50% increase in quartz sand compared to sandy soil, likely attributed to higher P adsorption to the sandy soil matrix than to quartz sand. Notably, only 60% of the absorbed 33 P was translocated to the shoot, with the remaining 40% directed to growing root tips of lateral or seminal roots. Phosphor imaging unveiled a continuous rise in 33 P signal in the labeled seminal root from immediate post-labeling until 24 hours after labeling. The highest 33 P activities were concentrated just above the labeled compartment, diminishing in locations farther away. Emerging laterals from the labeled root served as strong sinks for 33 P, while a portion was also transported to other seminal roots.Our study quantitatively visualized 33 P uptake and translocation dynamics, facilitating future investigations into diverse root regions/types and varying plant growth conditions. This improves our understanding of the significance of different P sources for plant nutrition and potentially enhances models of plant P uptake.